Leadership dans une perspective de genre - RGUIBI , Khalid; ATID , Asma (Revue Internationale du Chercheur, 2021)
It is clear that leadership is male-dominated and that women have certain advantages and disadvantages, as well as biases and a different leadership style. Consequently, the expectations of organizations of their employees in terms of assertiveness, availability and submission to hierarchy have always reflected the standard of living of men. Thus, the emergence of the concept of leadership has been shaped by male values. The gradual involvement of women in business life began in the 1970s. As a result, this small world tailored to men has led to the emergence of gender issues. While further research on leadership and gender is important to understand effective leadership practices for both men and women, there is also a body of research that suggests that organizations with a high representation of women in senior positions are more effective. We have focused on theoretical, conceptual evidence to explain and analyse the impact of gender on leadership and organizations.